The exceptions to patent rights under the WTO-TRIPS Agreement : where is the right to health guaranteed? - Wandrag, Riekie (University of Pretoria, 2006)
Prepared under the supervision of Riekie Wandrag at the Community Law Centre, University of Western Cape, South Africa